Generational differences in risk perception and situational uses of wine information sources. Issue 2 (29th November 2019) - Bauman, Matthew J.; Velikova, Natalia; Dodd, Tim; Blankenship, Trey
Abstract : Purpose: The purpose of this study is to examine generational differences in consumer Web 2.0 information source adoption for wine purchasing decisions, particularly social media and internet-based sources. Design/methodology/approach: An online survey resulted in 276 responses from wine consumers residing in Texas, USA. Information source usage was tested in two common purchasing situations: for casual and formal consumption. Chi-square analyses and ANOVA were used to examine differences among the generational cohorts in their use of information sources, levels of objective and subjective wine knowledge, wine involvement and risk perception for the two purchasing situations. Findings: Younger consumers were found to be significantly more inclined to use Web 2.0 information sources, such as wine blogs, wine applications, their contacts' recommendations on social media and wine experts on social media. Older consumers were more likely to use their own wine knowledge. Of greater interest is that in terms of their reliance on various wine information sources, Generation X behaves as the bridge between Generation Y and Baby Boomers. Generational differences regarding wine involvement, wine knowledge and risk perception also support this notion. Practical implications: The results of this study reinforce the need for wineries to adopt or create strategic initiatives using Web 2.0 elements. This study also suggests that depending on the purchasing context, consumers use certain information sources more than others. Originality/value: This research extends the understanding of the information acquisition process by expanding the types of information sources, and also yields valuable insights for consumers' off-premise wine purchasing decisions.